Magnetic resonance imaging and magnetic resonance spectroscopy in a young male patient with anti-N-methyl-D-aspartate receptor encephalitis and uncommon cerebellar involvement: A case report with review of the literature. Issue 1 (February 2016) - Splendiani, Alessandra; Felli, Valentina; Di Sibio, Alessandra; Gennarelli, Antonio; Patriarca, Lucia; Stratta, Paolo; Di Cesare, Ernesto; Rossi, Alessandro; Massimo, Gallucci
We report a case of a 17-year-old man presenting with new onset psychiatric symptoms. Magnetic resonance imaging (MRI) and proton magnetic resonance (MR) spectroscopy revealed some lesions in the right cerebellar hemisphere and ipsilateral cerebellar tonsil suggestive of encephalitis. An extensive workup was negative for both infectious and neoplastic diseases and he was afterward diagnosed with anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis. This disorder is an autoimmune encephalitis, highly lethal but curable, predominantly found in young female with ovarian teratoma. He received methylprednisolone. His clinical findings gradually improve and he made a complete recovery. Accordingly, repeated brain MRI and proton MR spectroscopy showed a gradual reduction of the lesions; MRI taken six months after starting therapy showed complete resolution of the lesions. Our case shows that, although rare, anti-NMDAR encephalitis should be considered also in young men for whom a rapid onset of psychiatric neurological disorders cannot be explained by more frequent causes. Our report underlines also the usefulness of MRI and proton MR spectroscopic findings in the diagnosis and follow-up of this disease.